Polarization and Exposure to Cross-Partisan Media in an Electoral Autocracy - Jeremy Bowles; Horacio Larreguy; Shelley Liu; Ahmet Akbiyik (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Political polarization is an increasing global concern. Although recent research suggests that media exposure can mitigate polarization through persuasion, it is unclear whether polarized individuals are willing to engage with diverse news sources, especially in electoral autocracies where citizens may distrust state-aligned media outlets or lack familiarity with credible alternatives. We implemented a field experiment in Türkiye exposing citizens to cross-partisan online media sources over seven months, which increased participants' consumption of assigned outlets across the board. We find evidence of ideological moderation with important asymmetries. While assignment to pro-government media durably bolstered appraisals of the ruling party and increased vote intentions, assignment to anti-government media, while increasing affinity for opposition parties, had narrower and shorter-lasting impacts. Distinct logics explain these differences: while participants came to trust and learn more about anti-government outlets, the broader and more diverse coverage of pro-government outlets appears responsible for their persuasive impacts. Our findings highlight both the potential and limits of media exposure to shift political views in polarized electoral autocracies.
Keywords: C93; D72; D83; 330; polarization; cross-partisan media; electoral autocracy